Palladium-Catalyzed Carbonyl-Retention Suzuki–Miyaura Coupling between N-Hydroxybenzotriazole Esters and Boronic Acids - Li, Shangzhang; Bai, Jin; Zhu, Riqian; Li, Wanfang (Synlett, 2023)
We have developed a palladium-catalyzed C–O bond activation of N-hydroxybenzotriazole esters, which represent a new type of electrophilic partner for Suzuki–Miyaura cross-coupling reactions to make various ketones. This reaction employed the cheap and commercially available PdCl2(MeCN)2/PCy3 as the catalyst and proceeded at 80 °C.
Keywords: palladium catalysis; Suzuki–Miyaura coupling; C–O bond activation; activated esters; ketone synthesis; N-hydroxybenzotriazole